Steeling the race: "Green steel" as the new clean material in the automotive sector - Hasan Muslemani; Francisco Ascui; Liang Xi; Katharina Kaesehage; Jeffrey Wilson (The Oxford Institute for Energy Studies, 2022)
This paper aims to examine consumer behaviour towards, and the willingness to adopt, 'green steel' in the automotive sector. Semi-structured interviews were held with experts from global, regional and country-specific industry associations and automakers. This paper appraises potential demand for green steel within different vehicle types (based both on size and powertrain) and shows that manufacturers of electric heavy-duty vehicles are most likely to be the first adopters of green steel. A case for green advanced higher-strength steels (AHSS) can also be made in light-duty passenger vehicles, which may mitigate competition from alternative lightweight materials in terms of cost and greenness (depending on source and utilization regions). This work emphasizes a need to revisit current CO2 performance regulations, engage in educational green marketing campaigns, and explore innovative market-based mechanisms to bridge the gap between relatively-low carbon abatement costs of steelmaking and high abatement costs of vehicle manufacturing.
Keywords: 330; automotive sector; carbon abatement; consumer behaviour; green marketing; Green steel; Regulations; steelmaking